2021
DOI: 10.3389/fimmu.2021.724855
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Susceptibility of ADAP-Deficient Mice to Listeria monocytogenes Infection Is Associated With an Altered Phagocyte Phenotype and Function

Abstract: The adhesion and degranulation-promoting adaptor protein (ADAP) serves as a multifunctional scaffold and is involved in the formation of immune signaling complexes. To date, only limited data exist regarding the role of ADAP in pathogen-specific immunity during in vivo infection, and its contribution in phagocyte-mediated antibacterial immunity remains elusive. Here, we show that mice lacking ADAP (ADAPko) are highly susceptible to the infection with the intracellular pathogen Listeria monocytogenes (Lm) by sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…FYB1 plays a crucial role in congenital autosomal recessive thrombocytopenia (CARST) [17], which manifest as abnormalities in platelet number and function, leading to an increased risk of bleeding. FYB1 also plays a role in autoimmune encephalomyelitis [18]. Addombati et al reported an association between FYB gene polymorphism and SLE; specifically, 2 out of 10 single nucleotide polymorphisms in the FYB1 gene were associated with SLE susceptibility [19].…”
Section: Introductionmentioning
confidence: 99%
“…FYB1 plays a crucial role in congenital autosomal recessive thrombocytopenia (CARST) [17], which manifest as abnormalities in platelet number and function, leading to an increased risk of bleeding. FYB1 also plays a role in autoimmune encephalomyelitis [18]. Addombati et al reported an association between FYB gene polymorphism and SLE; specifically, 2 out of 10 single nucleotide polymorphisms in the FYB1 gene were associated with SLE susceptibility [19].…”
Section: Introductionmentioning
confidence: 99%